PRADHAN MANTRI JAN DHAN YOJANA (PMJDY) - A CONCEPTUAL STUDY - Sharma, Neha; Goyal, Ruchi (International Journal of Research -GRANTHAALAYAH, 2017)
A successful development is marked with the establishment of a stable and useful financial system for the entire population. Indian government implemented many initiatives since independence for financial inclusion and recently launched Pradhan Mantri Jan-Dhan Yojana (PMJDY) to overcome the loopholes of previous initiatives. PMJDY is major financial plan with the objective of covering all households in the country with banking facilities along with inbuilt insurance coverage. With this background, the study has been conducted and tries to find out the success rate of inclusion process in rural areas of Jaipur district. For the purpose of the study, both primary data and secondary data have been collected. Correlation (r) test is used to find out the relationship between the socio economic backgrounds and the financial inclusion process. Findings show that Income, financial information from various channels and awareness of PMJDY are influential factors leading to inclusion. Nearness to banks increases the likelihood of inclusion.